1949
DOI: 10.1139/cjr49b-023
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and Spectrometric Studies of Some Pyrazolones

Abstract: Fourteen pyrazolones were synthesized from the corresponding mono or disubstituted cyanoacethydrazides or cyanoacetphenylhydrazides and evidence concerning their constitution was obtained from chemical reactions and ultraviolet absorption spectra determinations. A mixture of two tautomeric forms was obtained when 4-benzyl-3-amino-5-pyrazolone was prepared; it was converted to a single form by treatment with hydrochloric acid. The following compounds, as far as the authors are aware, have been prepared for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1952
1952
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…There is evidence that acids catalyze the transfornlation of one tautomeric form (VIII) into the other (IX). This \\.as observed with 4-benzyl-3-amino-5-pyrazolone (9).…”
Section: Co Nhsupporting
confidence: 56%
See 3 more Smart Citations
“…There is evidence that acids catalyze the transfornlation of one tautomeric form (VIII) into the other (IX). This \\.as observed with 4-benzyl-3-amino-5-pyrazolone (9).…”
Section: Co Nhsupporting
confidence: 56%
“…It has been demonstrated that pyrazolones of structure I X like 4-alky1-3-amino-2-phenyl-5-pyrazolones (9) have their ~n a x i~n u m abso&ion in the range from 2350 to 2450 A, whereas pyrazolones of structure VIII like 4-alkyl-3-amino-5-pyrazolones absorb in the range from 2750 to 2850 A (9).…”
Section: Co Nhmentioning
confidence: 99%
See 2 more Smart Citations
“…The first reports on 3-pyrazolidinones date to the 1940s. [1][2][3][4][5][6] Since that time, the importance of 3-pyrazolidinones has risen significantly, due to their applicability in industrial processes and biological activity. So far, progress on 3-pyrazolidinone chemistry has been reviewed by Dorn in 1981, 7 Claramunt and Elguero in 1991, 8 and in part by Svete in 2008.…”
Section: Introductionmentioning
confidence: 99%